Plant history and soil history jointly influence the selection environment for plant species in a long‐term grassland biodiversity experiment. Issue 12 (11th May 2021) - Dietrich, Peter; Eisenhauer, Nico; Otto, Peter; Roscher, Christiane
Abstract: Long‐term biodiversity experiments have shown increasing strengths of biodiversity effects on plant productivity over time. However, little is known about rapid evolutionary processes in response to plant community diversity, which could contribute to explaining the strengthening positive relationship. To address this issue, we performed a transplant experiment with offspring of seeds collected from four grass species in a 14‐year‐old biodiversity experiment (Jena Experiment). We used two‐ and six‐species communities and removed the vegetation of the study plots to exclude plant–plant interactions. In a reciprocal design, we transplanted five "home" phytometers (same origin and actual environment), five "away‐same" phytometers (same species richness of origin and actual environment, but different plant composition), and five "away‐different" phytometers (different species richness of origin and actual environment) of the same species in the study plots. In the establishment year, plants transplanted in home soil produced more shoots than plants in away soil indicating that plant populations at low and high diversity developed differently over time depending on their associated soil community and/or conditions. In the second year, offspring of individuals selected at high diversity generally had a higher performance (biomass production and fitness) than offspring of individuals selected at low diversity, regardless of the transplant environment. This suggests that plants at low and high diversity showed rapid evolutionary responses measurable in their phenotype. Our findings provide first empirical evidence that loss of productivity at low diversity is not only caused by changes in abiotic and biotic conditions but also that plants respond to this by a change in their micro‐evolution. Thus, we conclude that eco‐evolutionary feedbacks of plants at low and high diversity are critical to fully understand why the positive influence of diversity on plant productivity is strengthening through time. Abstract : We performed a transplant experiment with offspring of seeds collected in 14‐year‐old plant communities differing in plant species richness. Our findings provide evidence that low and high plant diversity and associated differences in soil community and/or conditions differentially influence eco‐evolutionary feedbacks of plants. ​